Changes in selected haematological parameters associated with JAK1/JAK2 inhibition observed in patients with rheumatoid arthritis treated with baricitinib. Issue 3 (6th October 2020) - Kay, Jonathan; Harigai, Masayoshi; Rancourt, Josh; Dickson, Christina; Melby, Thomas; Issa, Maher; de la Torre, Inmaculada; Isaka, Yoshitaka; Cardoso, Anabela; Saifan, Chadi; Keystone, Edward C; van Vollenhoven, Ronald F; et al.
Abstract : Objective: To characterise changes in selected haematological parameters following once-daily oral baricitinib dosing. Methods: Data were pooled from eight randomised clinical trials (four phase 3, three phase 2, one phase 1b) and one long-term extension. Changes in haematological parameters were evaluated up to 128 weeks (N=2387); overall safety of baricitinib was assessed up to 6 years (N=3492). Results: Mean absolute neutrophil counts decreased (−1.36×10 9 /L) within 1 month, followed by stabilisation within the normal reference range through week 128. The incidence of serious infections was not elevated in patients with neutropenia during the 24-week placebo-controlled period. Mean lymphocyte counts increased (+0.30×10 9 /L) within 1 month, then decreased to baseline (weeks 12–24). Mean platelet counts increased at week 2 (+51×10 9 /L), then decreased towards baseline. Overall, mean haemoglobin concentrations decreased (−0.12 mmol/L), then returned to baseline; however, reduced baseline haemoglobin concentrations observed in the highest baseline high-sensitivity C reactive protein quartile increased over time. Permanent drug discontinuation occurred due to laboratory abnormalities related to neutrophil count in 8 (0.2%), lymphocyte counts in 6 (0.2%), platelet counts in 8 (0.2%), and haemoglobin levels in 16 (0.5%) of all baricitinib-treated patients (N=3492 with 7993 total person-years of exposure). Conclusions: Moderate decreases in neutrophils were seen during baricitinib treatment; however, serious infection was uncommon in patients with neutropenia. Transient increases were observed in lymphocytes and platelets, which returned to baseline over time. Changes in haemoglobin concentration were generally small. Haematological abnormalities seldom led to drug discontinuation.